Atopic dermatitis in West Highland white terriers – Part III: early life peripheral blood regulatory T cells are reduced in atopic dermatitis. Issue 3 (9th February 2021) - Rostaher, Ana; Rodriguez‐Campos, Sabrina; Deplazes, Peter; Zwickl, Lena; Akdis, A. Cezmi; Urwyler, Adrian; Wheeler, David W.; Audergon, Sabrina; Fischer, Nina Maria; Favrot, Claude
Abstract : Background: Regulatory T (Treg) cells are involved in homeostasis of immune regulation and suppression of inflammation and T‐cell polarisation. Current knowledge regarding the role of Treg cells in the initiation of allergic disease is limited for both people and dogs. Objectives: To explore the role of circulating Treg cells and their possible influencing factors, on the development of atopic dermatitis (AD). Methods and materials: This study followed part of a birth cohort of West Highland white terrier dogs and classified them according to eventual clinical signs of AD (i.e. allergic versus healthy). The Treg phenotypes were assessed longitudinally by flow cytometry at 3, 3–12 and 12–36 months of age, and associated with development of AD. Different early life antigenic factors [endotoxins and allergens in house dust, Toxocara canis ‐specific immunoglobulin (Ig)E/IgG, allergen‐specific and total IgE, skin microbiota] were measured at three months of age, and a possible association with Treg cell levels was assessed. Results: The percentages of CD4 + CD25 + Foxp3 + Treg cells in healthy dogs were significantly higher at in 3‐month‐old (mean 4.5% healthy versus 3.3% allergic; P = 0.021) and <1‐year‐old (4.0% healthy versus 2.9% allergic; P = 0.028) dogs when compared to percentages of Treg cells in dogs that developed AD. There was a significantly positive correlation between the relative abundance of Lachnospiraceae on the skin and CD4 + CD25 + Foxp3 + Treg cells in puppies that became allergic ( r = 0.568, P = 0.017). Conclusion and clinical importance: Further large‐scale studies are needed to identify the practical value of these findings in AD diagnosis, treatment and prevention. Abstract : Background – Regulatory T (Treg) cells are involved in homeostasis of immune regulation and suppression of inflammation and T‐cell polarisation. Current knowledge regarding the role of Treg cells in the initiation of allergic disease is limited for both people and dogs. Objectives – To explore the role of circulating Treg cells and their possible influencing factors, on the development of atopic dermatitis (AD). Conclusion and clinical importance – Further large‐scale studies are needed to identify the practical value of these findings in AD diagnosis, treatment and prevention. Résumé: Contexte: Les cellules Treg sont impliquées dans l'homéostasie de la régulation immunitaire et la suppression de l'inflammation et de la polarisation cellulaire T. La connaissance actuelle du rôle des cellules T reg dans l'initiation de l'allergie est limitée chez le chien comme chez l'homme. Objectifs: Explorer le rôle des cellules T reg circulantes et leur possible facteurs d'influence sur le développement de la dermatite atopique (AD). Méthodes: Cette étude suit une part de cohorte de naissance du West Highland terrier et les classe selon d'éventuels signes cliniques d'AD (i.e. allergique versus sain). Les phénotypes Treg sont évalués longitudinalement par cytométrie de flux à l'âge de 3, 3‐12 et 12‐36 mois, et associés avec le développement de l'AD. Différents facteurs antigéniques de vie précoce (endotoxines et allergènes de la poussière de maison, immunoglobuline (Ig)E/IgG spécifiques de Toxocara canis, IgE totaux et spécifiques d'allergènes, microbiote cutané) ont été mesurés à l'âge de trois mois, et une association possible avec les niveaux de cellules Treg a été évaluée. Résultats: Les pourcentages de cellules Treg CD4+CD25+Foxp3+ chez les chiens sains étaient significativement plus élevés chez les chiens à l'âge de 3 mois (moyenne 4.5% sain versus 3.3% allergique; P = 0.021) et <1 an (4.0% sain versus 2.9% allergique; P = 0.028) lorsque comparés aux pourcentages de cellules Treg chez les chiens qui ont développés l'AD. Il y a avait une corrélation positive significative entre la relative abondance de Lachnospiraceae sur la peau et les cellules Treg CD4+CD25+Foxp3+ des chiots devenus allergiques (r = 0.568, P = 0.017). Conclusion et importance clinique: Des études à plus large échelle sont nécessaires pour identifier la valeur pratique de ces données dans le diagnostic, le traitement et la prévention de l'AD. Resumen: Introducción: las células T reguladoras (Treg) participan en la homeostasis de la regulación inmunitaria y de la supresión de la inflamación, y en la polarización de las células T. El conocimiento actual sobre el papel de las células Treg en el inicio de una enfermedad alérgica es limitado tanto para las personas como para los perros. Objetivos: Explorar el papel de las células Treg circulantes y sus posibles factores de influencia en el desarrollo de la dermatitis atópica (AD). Métodos: este estudio siguió parte de unas camadas de perros West Highland White Terrier y los clasificó de acuerdo con los posibles signos clínicos de la AD (es decir, alérgico frente a saludable). Los fenotipos Treg se evaluaron longitudinalmente mediante citometría de flujo a los 3, 3–12 y 12–36 meses de edad, y se asociaron con el desarrollo de AD. Se midieron diferentes factores antigénicos en la vida temprana [endotoxinas y alérgenos en el polvo doméstico, inmunoglobulina (Ig)E/IgG específica de Toxocara canis, IgE total y específica de alérgeno, microbiota cutánea] a los tres meses de edad y se evaluó una posible asociación con niveles de células Treg. Resultados: los porcentajes de células Treg CD4+CD25+Foxp3+ en perros sanos fueron significativamente más altos a los 3 meses de edad (media 4, 5% sanos frente a 3, 3% alérgicos; P = 0, 021) y <1 año (4, 0% sanos versus 2, 9% perros alérgicos; P = 0, 028) en comparación con los porcentajes de células Treg en perros que desarrollaron AD. Hubo una correlación significativamente positiva entre la abundancia relativa de Lachnospiraceae en la piel y las células Treg CD4+CD25+Foxp3+ en cachorros que desarrollaron alergia (r = 0, 568, P = 0, 017). Conclusión e importancia clínica: se necesitan más estudios a gran escala para identificar el valor práctico de estos hallazgos en el diagnóstico, el tratamiento y la prevención de la AD. Zusammenfassung: Hintergrund: Die regulatorischen T (Tregs) Zellen sind bei der Homöostase der Immunregulierung und der Supprimierung der Entzündung und Polarisierung der T‐Zellen involviert. Das momentane Wissen in Bezug auf die Rolle der Tregs Zellen beim Auslösen allergischer Erkrankungen ist auf Menschen und Hunde beschränkt. Ziele: Eine Erforschung der Rolle der zirkulierenden Tregs Zellen und ihrer möglichen Einflussfaktoren auf die Entwicklung einer atopischen Dermatitis (AD). Methoden: Diese Studie folgte einer Geburtskohorte von West Highland White Terriern und teilte sie entsprechend ihrer klinischen Zeichen von AD (i.e. allergisch versus gesund) ein. Die Treg Phänotypen wurden longitudinal mittels Flowzytometrie nach 3, 3‐12 und 12‐36 Altersmonaten erfasst, und mit der Entwicklung der AD in Zusammenhang gestellt. Unterschiedliche Antigenfaktoren im frühen Leben [Endotoxine und Allergene im Hausstaub, Toxocara canis‐spezifisches Immunglobulin (Ig)E/IgG, Allergen‐spezifisches und Total IgE, Haut Mikrobiota] wurden in einem Alter von drei Monaten gemessen und ein möglicher Zusammenhang mit der Anzahl der Tregs Zellen untersucht. Ergebnisse: Die Prozentanteile von CD4+CD25+Foxp3+ Treg Zellen waren bei gesunden Hunden signifikant höher als bei 3 Monate alten (Durchschnitt 4, 5% gesunde versus 3, 3% allergische; P = 0, 021) und <1 Jahr alten (4, 0% gesunde versus 2, 9% allergische; P = 0, 028) Hunden im Vergleich zum Prozentsatz an Treg Zellen bei Hunden, die AD entwickelten. Es bestand eine signifikant positive Korrelation zwischen der relativen Häufigkeit von Lachnospiraceae auf der Haut und CD4+CD25+Foxp3+ Treg Zellen bei Welpen, die Allergien entwickelten (r = 0, 568, P = 0, 017). Schlussfolgerungen und klinische Bedeutung: Weitere großangelegte Studien sind nötig, um den praktischen Wert dieser Ergebnisse bei der Diagnose, der Behandlung und der Prävention von AD zu identifizieren. 要約: 背景: 制御性T(Treg) 細胞は、免疫調節の恒常性の維持、炎症やT細胞の分極抑制に関与している。アレルギー疾患の発症における Treg 細胞の役割についての現在の知見は、人でも犬でも限られている。 目的: 本研究の目的は、アトピー性皮膚炎 (AD) の発症における循環Treg細胞の役割およびその影響因子の可能性を探る事であった。 方法: 本研究では、ウエスト・ハイランド・ホワイト・テリアの出生コホートの一部を追跡調査し、最終的なADの臨床症状 (アレルギー対健常) に応じて分類した。Tregの表現型を、生後3ヶ月、3 12ヶ月、12 36ヶ月のフローサイトメトリー法で縦断的に評価し、AD発症と関連付けた。異なる初期の抗原性因子 (ハウスダスト中のエンドトキシンやアレルゲン、Toxocara canis特異的免疫グロブリン (Ig)E/IgG、アレルゲン特異的IgEおよび総IgE、皮膚微生物叢) を生後3ヵ月で測定し、Treg細胞レベルとの関連性の可能性を評価した。 結果: 健常犬のCD4+CD25+Foxp3+ Treg細胞の割合は、AD発症犬のTreg細胞の割合と比較して、生後3ヶ月 (平均4.5%、アレルギー3.3%、P=0.021) および1歳未満 (4.0%、アレルギー2.9%、P=0.028) の犬で有意に高かった。アレルギー発症の子犬の皮膚上のラクノスピラ科の相対量およびCD4+CD25+Foxp3+ Treg細胞間には有意な正の相関があった (r = 0.568, P = 0.017) 。 結論と臨床上の重要性: ADの診断、治療、予防におけるこれらの知見の実用的価値を明らかにするためには、さらなる大規模な研究が必要である。 Abstract : 背景: 调节性T(Treg)细胞参与免疫调节的稳态以及炎症和T细胞极化的抑制。目前关于Treg细胞在过敏性疾病初期的作用, 人和犬的相关知识都很有限。 目的: 探索循环Treg细胞及其可能的影响因素在特应性皮炎(AD)发生中的作用。 方法: 本研究跟踪了一批相同血统的西高地白㹴犬, 并根据AD的最终临床体征对其进行分类 (即过敏与健康) 。在3、3‐12和12‐36月龄时, 通过流式细胞术纵向评估Treg表型, 以及发生AD的相关性。在3月龄时检测不同的生命早期抗原因子[屋尘的内毒素和过敏原、弓首蛔虫特异性免疫球蛋白(Ig)E/IgG、过敏原特异性和总IgE、皮肤微生物群], 并评估与Treg细胞水平的可能关联。 结果: 与AD患犬的Treg细胞百分比相比, 3月龄 (健康犬平均4.5%与过敏犬3.3%;P=0.021) 和 <1岁 (健康犬4.0%与过敏犬2.9%;P=0.028) 健康犬的CD4+CD25+Foxp3+Treg细胞百分比显著更高。过敏幼犬皮肤上, 毛螺旋菌相对丰度与CD4+CD25+Foxp3+Treg细胞呈显著正相关(r=0.568, P=0.017)。 结论和临床重要性: 需要更多大规模研究来确定这些发现在AD诊断、治疗和预防中的实用价值。 Resumo: Contexto: As células T reguladoras (Treg) estão envolvidas na homeostase da regulação imunológica e na supressão da inflamação e polarização das células T. O conhecimento atual sobre o papel das células Treg no início da doença alérgica é limitado tanto para pessoas quanto para cães. Objetivos: Explorar o papel das células Treg circulantes e seus possíveis fatores influenciadores no desenvolvimento da dermatite atópica (DA). Métodos: Este estudo acompanhou parte de uma coorte de nascimento de cães West Highland white terrier e os classificou de acordo com eventuais sinais clínicos de DA (alérgicos versus saudáveis). Os fenótipos Treg foram avaliados longitudinalmente por citometria de fluxo aos 3, 3–12 e 12–36 meses de idade e associados ao desenvolvimento da DA. Diferentes fatores antigênicos do início da vida [endotoxinas e alérgenos na poeira doméstica, imunoglobulina (Ig) E / IgG específica para Toxocara canis, IgE total e IgE alérgeno‐específica, microbiota da pele] foram medidos aos três meses de idade e uma possível associação com células Treg níveis foram avaliados. Resultados: As porcentagens de células Tregs CD4+CD25+Foxp3+ em cães saudáveis ​​foram significativamente maiores aos 3 meses de idade (média de 4, 5% saudáveis ​​versus 3, 3% alérgicas; P = 0, 021) e em cães <1 ano (4, 0% saudáveis versus 2, 9% alérgicos; P = 0, 028) quando comparados às porcentagens de células Treg em cães que desenvolveram DA. Houve uma correlação significativamente positiva entre a abundância relativa de Lachnospiraceae na pele e células Tregs CD4+CD25+Foxp3+ em filhotes que se tornaram alérgicos (r = 0, 568, P = 0, 017). Conclusão e importância clínica: Mais estudos em larga escala são necessários para identificar o valor prático desses achados no diagnóstico, tratamento e prevenção da DA.